Waist circumference cut-off points to identify major cardiovascular events and incident diabetes in Latin America: findings from the prospective Urban rural epidemiology study Colombia - Lopez-Lopez, Jose P.; Gonzalez, Ana María; Lanza, Paola; Martinez-Bello, Daniel; Gomez-Arbelaez, Diego; Otero, Johanna; Cohen, Daniel D.; Perez-Mayorga, Maritza; Garcia-Peña, Angel A.; Rangarajan, Sumathy; Yusuf, Salim; Lopez-Jaramillo, Patricio (Frontiers in Cardiovascular Medicine, 2023)
Background: Abdominal obesity (AO) indirectly represents visceral adiposity and can be assessed by waist circumference (WC) measurement. In Latin America, cut-off points for the diagnosis of AO are based on Asian population data. We aim to establish the WC cut-off points to predict major cardiovascular events (MACE) and incident diabetes. Methods: We analyzed data from the cohort PURE study in Colombia. WC cut-off points were defined according to the maximum Youden index. Multivariate logistic regression was used to obtain associations between WC and MACE, diabetes, and cumulative incidence of outcomes visualized using Kaplan-Meier curves. Results: After a mean follow-up of 12 years, 6580 individuals with a mean age of 50.7±9.7 years were included; 64.2% were women, and 53.5% were from rural areas. The mean WC was 85.2±11.6 cm and 88.3±11.1 cm in women and men, respectively. There were 635 cases of the MACE composite plus incident diabetes (5.25 events per 1000 person-years). Using a cut-off value of 88.85 cm in men (sensitivity= 0.565) and 85.65 cm in women (sensitivity= 0.558) resulted in the highest value for the prediction of the main outcome. These values were associated with a 1.76 and 1.41-fold increased risk of presenting the composite outcome in men and women, respectively. Conclusions: We defined WC cut-off points of 89 cm in men and 86 cm in women to identify the elevated risk of MACE and incident diabetes. Therefore, we suggest using these values in cardiovascular risk assessment in Latin America.